Chinese Adolescents' Influence on Family Decision Making - He, Shushi (2008)
The purpose of this study is to investigate Chinese adolescents' influence on family decision making regarding on the effect of children's characteristics including academic performance, product knowledge and financial saving. The concept of value alignment is initially introduced to the family decision making since it greatly concerns on the Chinese culture. It is assumed that China's only children would have more influence on the decision making of high-end electronic goods when they align with parental value of academic performance, product information seeking and financial saving respectively. The research employed self-report survey for gathering data. A convenient sample of seventy-seven matched pairs of adolescents age 15-19 and their mothers from only-child family was collected. The results indicate that the creation of value alignment by adolescents enhances Chinese adolescents' influence on family decision making and also moderates the effect of children's resource on the influence of family decision making.